Le tribunal figural de la fiction expressionniste - Sylvain Louet (Recherches Germaniques)
The article considers a singular film, Von morgens bis mitternachts, directed by Karl Heinz Martin in 1920. This fiction is a major work of the German expressionist current because of the originality of its visual inventions. The faces are painted and grimed. The sets appear unfinished and awkward. We compare this ethical film to works by expressionist painters or engravers to examine how it judges its main protagonists and the evoked society, considering the Christian morality and that promoted by capitalism. On the one hand, the scenic reverie and the motif of the fertile moment play an essential role. On the other hand, the genre of melodrama is renewed because the hero is judged through the figural secretion of evil and the motif of disfiguration.